Canada : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2011)
Canadian housing prices are higher than levels consistent with current fundamentals in some provinces. The empirical estimates suggest that a 10 percent decline in housing prices would lead to a 1u percent decline in private consumption. The high level of household leverage and housing prices could prove to be a source of vulnerability. The rebound in debt and housing prices after the crisis largely reflects the resilience of the financial system and the stronger economic recovery in Canada, as well as historically low interest rates.